How science works - Hann, Judith (Pleasantville, N.Y. : Reader's Digest Association, 1991)
Provides practical science experiments and projects designed to be completed at home with safe, everyday ingredients.
Includes index.
Booklist
Voice of Youth Advocates
8.4
5-8
Keywords: Scientific recreations; Science -- Experiments -- Popular works; Scientific recreations; Science -- Experiments